Performance of two egg parasitoids of brown marmorated stink bug before and after cold storage - Li, Wen-Jing; Chen, Ju-Hong; Avila, Gonzalo A.; Ali, Muhammad-Yasir; Tian, Xin-Yue; Luo, Zheng-Yu; Zhang, Feng; Shi, Shu-Sen; Zhang, Jin-Ping (Frontiers in Physiology, 2023)
Introduction: The genus Trissolcus includes a number of egg parasitoids that are known to contribute to the control of Halyomorpha halys. The number of progenies, particularly females, is important for the efficient mass rearing of species used in augmentative biological control programs. Cold storage is an important technique for extending the shelf life of natural enemies used in such programs. Methods: We assessed how fecundity, sex ratio, lifespan, and the number of hosts parasitized within 24 h were affected by host density for T. japonicus and T. cultratus when offered fresh H. halys eggs and how these parameters were affected if adult parasitoids were first placed in cold storage (11°C in the dark) for 19 weeks before being used for propagation. Results: The fecundity were 110.2 and 84.2 offspring emerged at 25°C, for parasitoids not placed in cold storage; among the offspring that emerged, 82.6% and 85.6% were female for T. japonicus and T. cultratus, respectively. If first placed in cold storage, T. japonicus and T. cultratus produced 35.1 and 24.6 offspring per female, respectively, although cold storage significantly extended the shelf life. The survival rates of parasitoids that were placed in cold storage were 90.3% and 81.3% for females, and 3.2% and 0.9% for males of T. japonicus and T. cultratus, respectively. The number of hosts parasitized within 24 h was not shown to be density dependent, but it was significantly lower after cold storage. Discussion: This information can be used to estimate the likely production for augmented rearing colonies for use in biological control programs.